Three tiered display of flowers and plants - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a circular three tiered display of flowers and plants at a garden show. A large tent pole appears in the center of the tiers. Lanterns and a couple of banners hang above. Material from a large tent appears above and behind this scene.